Genomic and virulent characterization of a duck-associated Salmonella serovar Potsdam from China - Hongli An; Xiamei Kang; Chenhu Huang; Chenghao Jia; Jiaqi Chen; Yingying Huang; Qianzhe Cao; Yan Li; Biao Tang; Min Yue (Poultry Science)
Salmonella, a common zoonotic pathogen, is a significant concern for public health, particularly when it contaminates animal-borne products. The potential for Salmonella to infect duck embryos and disrupt their normal development not only causes substantial economic losses for the industry but also poses a severe threat to public health. However, there is a lack of understanding about the prevalence of Salmonella in duck embryos and their potential public health implications. Our study aims to fill this gap by providing genomic features of the antimicrobial resistance and virulence potential of Salmonella isolates from dead duck embryos using whole-genome sequencing and in silico toolkits. We also sought to assess the virulent characterization of the major serovar isolates by experimental infection of chicken and duck embryos. Our investigation of 195 duck embryo eggs led to the isolation of 40 (20.51%) Salmonella strains, with Salmonella serovar Potsdam being the most prevalent serovar. Most isolates were resistant to streptomycin (57.3%) and nalidixic acid (50%). Notably, our findings demonstrated that S. Potsdam exhibited a preference for ducks over chickens, suggesting potential host specificity. Additionally, global phylogenomic analysis, incorporating 180 global genomes, revealed a predominant association of S. Potsdam with ducks, supporting an adaptive process specific to the waterfowl. This study determined Salmonella serovars and antimicrobial resistance profiles in dead duck embryos, revealing a rare Salmonella serovar Potsdam with a potential for duck adaption.